Chronic obstructive pulmonary disease - diagnosis and management of stable disease; a personalized approach to care, using the treatable traits concept based on clinical phenotypes. Position paper of the Czech Pneumological and Phthisiological Society - Zatloukal, Jaromir; Brat, Kristian; Neumannova, Katerina; Volakova, Eva; Hejduk, Karel; Kocova, Eva; Kudela, Ondrej; Kopecky, Michal; Plutinsky, Marek; Koblizek, Vladimir (Biomedical papers, 2020)
This position paper has been drafted by experts from the Czech national board of diseases with bronchial obstruction, of the Czech Pneumological and Phthisiological Society. The statements and recommendations are based on both the results of randomized controlled trials and data from cross-sectional and prospective real-life studies to ensure they are as close as possible to the context of daily clinical practice and the current health care system of the Czech Republic. Chronic Obstructive Pulmonary Disease (COPD) is a preventable and treatable heterogeneous syndrome with a number of pulmonary and extrapulmonary clinical features and concomitant chronic diseases. The disease is associated with significant mortality, morbidity and reduced quality of life. The main characteristics include persistent respiratory symptoms and only partially reversible airflow obstruction developing due to an abnormal inflammatory response of the lungs to noxious particles and gases. Oxidative stress, protease-antiprotease imbalance and increased numbers of pro-inflammatory cells (mainly neutrophils) are the main drivers of primarily non-infectious inflammation in COPD. Besides smoking, household air pollution, occupational exposure, low birth weight, frequent respiratory infections during childhood and also genetic factors are important risk factors of COPD development. Progressive airflow limitation and airway remodelling leads to air trapping, static and dynamic hyperinflation, gas exchange abnormalities and decreased exercise capacity. Various features of the disease are expressed unequally in individual patients, resulting in various types of disease presentation, emerging as the "clinical phenotypes" (for specific clinical characteristics) and "treatable traits" (for treatable characteristics) concept. The estimated prevalence of COPD in Czechia is around 6.7% with 3,200-3,500 deaths reported annually. The elementary requirements for diagnosis of COPD are spirometric confirmation of post-bronchodilator airflow obstruction (post-BD FEV1/VCmax <70%) and respiratory symptoms assessement (dyspnoea, exercise limitation, cough and/or sputum production. In order to establish definite COPD diagnosis, a five-step evaluation should be performed, including: 1/ inhalation risk assessment, 2/ symptoms evaluation, 3/ lung function tests, 4/ laboratory tests and 5/ imaging. At the same time, all alternative diagnoses should be excluded. For disease classification, this position paper uses both GOLD stages (1 to 4), GOLD groups (A to D) and evaluation of clinical phenotype(s). Prognosis assessment should be done in each patient. For this purpose, we recommend the use of the BODE or the CADOT index. Six elementary clinical phenotypes are recognized, including chronic bronchitis, frequent exacerbator, emphysematous, asthma/COPD overlap (ACO), bronchiectases with COPD overlap (BCO) and pulmonary cachexia. In our concept, all of these clinical phenotypes are also considered independent treatable traits. For each treatable trait, specific pharmacological and non-pharmacological therapies are defined in this document. The coincidence of two or more clinical phenotypes (i.e., treatable traits) may occur in a single individual, giving the opportunity of fully individualized, phenotype-specific treatment. Treatment of COPD should reflect the complexity and heterogeneity of the disease and be tailored to individual patients. Major goals of COPD treatment are symptom reduction and decreased exacerbation risk. Treatment strategy is divided into five strata: risk elimination, basic treatment, phenotype-specific treatment, treatment of respiratory failure and palliative care, and treatment of comorbidities. Risk elimination includes interventions against tobacco smoking and environmental/occupational exposures. Basic treatment is based on bronchodilator therapy, pulmonary rehabilitation, vaccination, care for appropriate nutrition, inhalation training, education and psychosocial support. Adequate phenotype-specific treatment varies phenotype by phenotype, including more than ten different pharmacological and non-pharmacological strategies. If more than one clinical phenotype is present, treatment strategy should follow the expression of each phenotypic label separately. In such patients, multicomponental therapeutic regimens are needed, resulting in fully individualized care. In the future, stronger measures against smoking, improvements in occupational and environmental health, early diagnosis strategies, as well as biomarker identification for patients responsive to specific treatments are warranted. New classes of treatment (inhaled PDE3/4 inhibitors, single molecule dual bronchodilators, anti-inflammatory drugs, gene editing molecules or new bronchoscopic procedures) are expected to enter the clinical practice in a very few years.
Keywords: COPD; position paper; clinical phenotypes; treatable traits; bronchodilators; individualized care; personalized medicine